Faculty Advising: Teaching, Research, or Service? - Wendy Troxel (Academic Chairpersons Conference Proceedings, 2018)
This interactive session explores the incentives (or lack of incentives) for faculty to see academic advising and mentoring as a fundamental and rewarding element of a career in higher education. Professional development to support faculty advising is also addressed.
Keywords: Advising; Faculty; Teaching; Research; Service